Features of event content and evaluation of significant life situations in persons with different levels of personal maturity - N. P. Andryushkova (Вестник университета, 2023)
The article examines personal maturity as a complex multicomponent phenomenon that can reach various levels of development. The relevance of the study of personal maturity through significant events of a person’s life path is noted. In order to identify the attitude towards the most significant life events and the specifics of interaction with the life situation, an empirical study was conducted and involved 277 people 25 to 40 years of age that represent the fields of education, medicine, service and trade, and mining industry. The subjects were divided into 2 groups according to their level of personal maturity and infantilism as polar characteristics. Based on the results of the study, the author points out significant differences in the experience and description of life events as well as the definition of significant life situations among subjects with different levels of personal maturity.